Errance and Elsewheres among Africans Waiting to Restart Their Journeys in Dakar, Senegal (2015)
ABSTRACT: This article analyzes the experience of Africans stranded in Dakar, Senegal, halfway through their intended journeys out of the continent. A number of forces such as regimes of border control and visa policies, a culturally rooted sense of adventure, historically established networks, and individual genius shape their itineraries. These forces lead them to Dakar, prevent the continuation of their journeys, and bend their routes and destinations toward the global South. I turn to the notions of errance and elsewheres to describe the spatial and temporal dimensions of this experience, its particular relation to national borders, and the sense of uncertainty pervading it. Errance can be understood as the quest for an acceptable place, while elsewheres describe imagined, distant, malleable destinations that invest a journey with purpose. They not only relate to the there and then of dreams and aspirations but structure relations to the here and now. Academic literatures on migration, economic crises, and border studies generally theorize the experience of being able to leave home in terms of suspension. I extend this literature by examining the ways in which space and time are experienced in an already-begun but interrupted journey. Past and future, actual and potential, destinations, routes, and frail transactions hint at different ways of understanding movement and stasis.